High-entropy NASICON oxide solid electrolyte and preparation method and application thereof

By introducing high-entropy NASICON oxide solid electrolytes with various metal elements, the problems of low room temperature conductivity and unstable to sodium in the existing NASICON structural electrolytes are solved, and the high room temperature conductivity and stability to sodium are achieved, and the performance of solid sodium batteries is improved.

CN119695265AActive Publication Date: 2025-03-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510198689.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing NASICON structural solid electrolyte has low room temperature conductivity and is unstable to sodium, which limits the application of solid sodium batteries.

Method used

High-entropy NASICON oxide solid electrolyte is used, and its chemical formula is Na3±iZr2-xMxSi2+yP1-yO12, and the conductivity and stability are improved by introducing a variety of metal elements (such as Zn, Ca, La, Yb, Cu, Mg, Sc, In, Y, Hf, Ge, Sb, Ta, Nb).

Benefits of technology

It achieves high room temperature conductivity and stability to sodium, and improves the cycle stability and limit current density of solid-state sodium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695265A_ABST
    Figure CN119695265A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid electrolytes, and particularly relates to a high-entropy NASICON oxide solid electrolyte and a preparation method and application thereof. The chemical general formula of the high-entropy NASICON oxide solid electrolyte is Na < 3 + / -iZr < 2-x > M < x > Si < 2 + y > P < 1-y > O < 12 >, 0 < = i < 1, 0 < x < 1, 0.25 < = y < = 0.5, and M is four or more of Zn, Mg, Cu, Ca, Sc, In, La, Yb, Y, Hf, Ge, Sb, Ta and Nb. The NASICON oxide solid electrolyte with a specific chemical formula is formed by introducing various metal elements into a solid electrolyte system with an NASICON structure, so that the ionic conductivity, the limiting current density and the sodium stability of the electrolyte are improved, and an assembled all-solid-state battery shows excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a high-entropy NASICON oxide solid electrolyte and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are considered one of the most competitive alternatives to lithium-ion batteries due to their significant advantages of low raw material costs and wide sources. However, the use of flammable organic electrolytes in traditional sodium-ion batteries poses safety hazards such as leakage, combustion, and even explosion, which greatly limits their further development and application. Against this background, NASICON structured solid electrolyte materials came into being. They have many advantages such as high safety performance, good stability, low cost, and environmental friendliness, which makes it possible to realize solid-state sodium batteries, and thus become a research hotspot in the field of energy storage.

[0003] Sodium ion solid electrolyte is the core part of solid-state sodium battery, which affects the safety and electrochemical performance of the battery. In order to achieve good application in solid-state sodium battery, sodium ion solid electrolyte needs to have high ionic conductivity and ion migration number, wide electrochemical window, good chemical stability and interface compatibility. According to the material composition, the existing sodium ion solid electrolyte can be mainly divided into polymer solid electrolyte, sulfide solid electrolyte, β-Al2O3 (Na2O-nAl2O3) solid electrolyte and NASICON (Na superionic conductor) structure solid electrolyte. Among them, NASICON structure solid electrolyte has a wide electrochemical window, low thermal expansion, cheap raw materials, easy preparation, and environmental friendliness. It is an ideal sodium ion solid electrolyte material. However, the electrolyte still has problems such as low room temperature conductivity and instability to sodium.

[0004] High entropy materials have attractive advantages, such as easy formation of single-phase solid solutions with simple crystal structures and customized functional properties, and have gained great attention in the fields of thermoelectricity, thermal energy and environmental protection, and electrochemical energy storage. All-solid-state inorganic high-entropy electrolytes are composed of a variety of ions, and there is no obvious ordered arrangement in their crystal structure. The diffusion paths of ions within the material become more diverse. This allows ions to migrate through different channels and positions, reducing mutual hindrance between ions and promoting the rate of ion migration. In crystals with long-range ordered structures, ions tend to form stable arrangements, resulting in stronger ion binding energy. In contrast, the ion binding energy between ions in high-entropy electrolytes that lack long-range order is much lower, making it easier for ions to dissociate and migrate.

[0005] From the perspective of resources, cost, safety and stability, solid-state sodium batteries are expected to play a huge role in large-scale energy storage applications. Therefore, in view of the low room temperature conductivity and instability of NASICON structured solid electrolytes to sodium, it is necessary to propose a new high-entropy NASICON oxide solid electrolyte with high room temperature conductivity and critical current density, as well as its preparation method and application. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a high-entropy NASICON oxide solid electrolyte and a preparation method and application thereof. The NASICON structured solid electrolyte has excellent sodium stability and high critical current density while ensuring relatively high ionic conductivity, and the assembled all-solid-state battery exhibits excellent cycle stability.

[0007] One aspect of the present invention is to provide a high entropy NASICON oxide solid electrolyte, the general chemical formula of which is Na 3±i Zr 2-x M x Si 2+y P 1-y O 12 , where 0≤i<1, 0<x<1, 0.25≤y≤0.5, and M is four or more of Zn, Mg, Cu, Ca, Sc, In, La, Yb, Y, Hf, Ge, Sb, Ta, and Nb.

[0008] Here, the atomic number x of M refers to the total atomic number of four or more elements.

[0009] Preferably, M is one or more of Cu, Ca, La, Yb and one or more of Zn, Mg, Sc, In, Y, Hf, Ge, Sb, Ta, and Nb, and the element types of M are four or more.

[0010] Preferably, the chemical formula is Na 3+i Zr 2-x M x Si 2+y P 1-y O 12 , where 0.4≤i≤0.9.

[0011] Preferably, in the general chemical formula, x is 0.05 to 0.5, more preferably 0.1 to 0.4.

[0012] Preferably, the room temperature ionic conductivity of the NASICON oxide solid electrolyte is ≥1×10 -3 S cm -1 , more preferably ≥1.5×10 -3 S cm -1, and further preferably ≥1.9×10 -3 S cm -1 , and further preferably 1.9×10 -3 ~8×10 -3 S cm -1 The room temperature here refers to the natural temperature indoors, ranging from 5 to 40 ℃.

[0013] The second aspect of the present invention is to provide a method for preparing a high entropy NASICON oxide solid electrolyte, comprising the following steps: (1) According to the general formula Na 3±i Zr 2-x M x Si 2+y P 1-y O 12 , respectively weighing a sodium source, a phosphorus source, a zirconium source, a silicon source and an M ion source in a stoichiometric ratio, performing a first wet mixing and drying, and further performing high temperature sintering, and obtaining a precursor powder after a second wet mixing and drying; (2) Precursor powder is mixed with a binder solution, isostatically pressed to form a green body, and then subjected to two-stage sintering to obtain the high-entropy NASICON oxide solid electrolyte.

[0014] Preferably, the sodium source is one or more of Na2CO3, NaNO3, Na2O, NaHCO3, and NaOH; the phosphorus source is one or more of NH4H2PO4, NaH2PO4, Na2HPO4, and P2O5; the zirconium source is ZrO2; the silicon source is SiO2; and the M ion source is an oxide of the M element, specifically four or more of ZnO, MgO, CuO, CaO, Sc2O3, In2O3, La2O3, Yb2O3, Y2O3, HfO2, GeO2, Sb2O5, Ta2O5, and Nb2O5.

[0015] Preferably, the wet mixing method is mechanical ball milling or high-energy ball milling, the ball-to-material ratio is (2-6):1, the ball milling speed is 200-600 rpm, the ball milling time is 2-12 hours, and the ball milling solvent is one or more of anhydrous ethanol, isopropanol, n-propanol, acetone, and butanol. The first wet mixing and the second wet mixing can be the same or different.

[0016] The drying may be carried out by any means capable of evaporating the solvent, such as vacuum drying, forced air drying, etc. The drying temperature is 40 to 90°C.

[0017] Preferably, the high temperature sintering conditions of step (1) are: 500-1200° C., 2-24 hours in a pure oxygen atmosphere.

[0018] Preferably, in step (2), the mass ratio of the precursor powder to the binder solution is (10-50):1.

[0019] Preferably, the binder solution is formed by dissolving the binder in a solvent. The concentration of the binder solution is 1-800 mg / ml.

[0020] Preferably, the binder is one or more of polyvinyl alcohol, polyvinyl butyral, polydopamine, and polyacrylic acid.

[0021] Preferably, in step (2), the isostatic pressing pressure is 10-700 MPa, and the pressure holding time is 1 min-4 h.

[0022] Preferably, in step (2), the two-stage sintering includes a first-stage sintering and a second-stage sintering. The temperature of the first-stage sintering is 550-900°C, and the sintering time is 1-4 hours; the temperature of the second-stage sintering is 1100-1300°C, and the sintering time is 2-24 hours. The two-stage sintering is performed in a pure oxygen atmosphere.

[0023] The third aspect of the present invention is to provide an all-solid-state sodium secondary battery, comprising a positive electrode, a negative electrode and the high-entropy NASICON oxide solid electrolyte.

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a high-entropy NASICON oxide solid electrolyte with a high critical current density. A variety of metal elements are introduced into the NASICON structure solid electrolyte system. The introduced chemical disorder and distortion will disrupt and redistribute the local site energy. When this distribution is wide enough to achieve energy overlap between adjacent sites, it will promote Na+ hopping. The doped high-entropy NASICON oxide solid electrolyte has high ionic conductivity and limiting current density.

[0025] 2. The various metal elements introduced in the present invention can cause local disorder in the high-entropy NASICON oxide solid electrolyte. This disorder effectively promotes site percolation through overlapping site energy distribution, thereby preventing the growth of sodium dendrites and preparing a high-entropy NASICON oxide solid electrolyte with excellent stability to sodium metal.

[0026] 3. The high entropy NASICON oxide solid electrolyte provided by the present invention has high ionic conductivity and sodium stability. Furthermore, the sodium / / sodium symmetric battery assembled by the oxide solid electrolyte is better than Na3Zr2Si2PO 12The sodium / / sodium symmetric battery assembled with oxide solid electrolyte has better cycling stability to sodium. In addition, the high entropy NASICON oxide solid electrolyte with high critical current density of the present invention is assembled into an all-solid-state battery, which exhibits excellent cycling stability.

[0027] 4. The doping elements of the present invention are further preferably M is one or more of Cu, Ca, La, Yb and one or more of Zn, Mg, Sc, In, Y, Hf, Ge, Sb, Ta, Nb, and the element types of M are four or more. The doping of Cu, Ca, La, and Yb elements is beneficial to improving the ionic conductivity, limiting current density, and sodium stability of the high entropy NASICON oxide solid electrolyte, and the battery prepared therefrom has better cycle stability.

[0028] 5. The high-entropy NASICON oxide solid electrolyte provided by the present invention has excellent sodium stability and high critical current density while ensuring high ionic conductivity.

[0029] 6. The method for preparing the high-entropy NASICON oxide solid electrolyte provided by the present invention is simple to operate, highly practical, and convenient for large-scale production. Preferably, two-stage sintering is adopted, which is beneficial to improving performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Scanning electron microscope image and X-ray energy spectrum scanning element distribution map of oxide solid electrolyte; Figure 2 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 X-ray diffraction spectrum of oxide solid electrolyte; Figure 3 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12AC impedance spectroscopy of oxide solid electrolytes; Figure 4 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Limiting current density curve of sodium||sodium symmetric battery with oxide solid electrolyte; Figure 5 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Comparison of electronic conductivity of oxide solid electrolytes; Figure 6 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Comparison of activation energies of the oxide solid electrolyte and the Na3Zr2Si2PO12 oxide solid electrolyte of Comparative Example 1; Figure 7 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Long cycle curve of sodium||sodium symmetric battery with oxide solid electrolyte; Figure 8 is Na of Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Long cycle curve of all-solid-state battery with oxide solid electrolyte at 1C rate.

[0031] Fig. 9is Na of Example 14 of the present invention 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Long cycle curve of sodium||sodium symmetric battery with oxide solid electrolyte; Fig.10 is Na of Example 14 of the present invention 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 Long cycle curve of all-solid-state battery with oxide solid electrolyte at 1C rate. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art. Example 1

[0033] This embodiment Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 (i.e. Na 3.6 Zr 1.8 Zn 0.05 Ca 0.05 Sc 0.05 La 0.05 Si 2.3 P 0.7 O 12 ) The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, ZnO, CaO, Sc2O3, and La2O3 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven for 80 Dry the solvent at ℃.

[0034] (2) The dried powder was ground evenly in an agate mortar and placed in a tube furnace for sintering. The sintering atmosphere was pure oxygen, the sintering temperature was 900 degrees, and the sintering time was 12 hours. The sintered powder was placed in an agate ball mill again, and zirconium oxide balls were added according to the ball-to-material ratio of 5:1. Anhydrous ethanol was added, and the ball milling speed was 400 rpm. The ball milling time was 8 hours. After the ball milling was completed, the mixed material was placed in a blast drying oven for 80 ℃ drying solvent, get Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Precursor.

[0035] (3) Weigh a certain mass of Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The precursor was mixed with polyvinyl alcohol aqueous solution (concentration of 10 mg / ml) (Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The precursor and polyvinyl alcohol aqueous solution (mass ratio of 40:1) were placed in a customized mold and made into a green body by isostatic pressing. The pressure used was 200MPa and the pressure holding time was 5 minutes. The green body was placed in a tubular furnace for two-stage sintering. The sintering atmosphere was pure oxygen. The first stage sintering temperature was 700 degrees and sintering was for one hour; the second stage sintering temperature was 1250 degrees and the sintering time was 6 hours. After annealing, a high-entropy NASICON oxide solid electrolyte sheet was obtained.

[0036] Figure 1 The Na prepared in Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O12 Scanning electron microscope image and X-ray spectrum scanning element distribution map of oxide solid electrolyte. From the surface scanning element distribution map, it can be seen that Zn, Mg, Sc, and Hf elements are evenly distributed in Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0037] Figure 2 is the Na prepared in Example 1 of the present invention 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte and Na3Zr2Si2PO4 of Comparative Example 1 12 The X-ray diffraction spectrum of the oxide solid electrolyte shows that the main phase of the high-entropy NASICON oxide solid electrolyte of this embodiment is a monoclinic phase, and no impurity phase is generated.

[0038] Performance testing and battery assembly 1) By ion sputtering in Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 4.24×10 -3 S cm -1 , relative to Na3Zr2Si2PO in Comparative Example 1 12 The ionic conductivity of oxide solid electrolytes has increased by about 11 times. Figure 3 shown.

[0039] 2) Using metallic sodium as the symmetrical electrode, Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 10 mA cm -2 The high current density is comparable to that of Na3Zr2Si2PO 12Compared with oxide solid electrolytes, it exhibits excellent resistance to sodium dendrites (see Figure 4 ).

[0040] 3) By ion sputtering in Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 2.47×10 -9 S cm -1 , relative to Na3Zr2Si2PO in Comparative Example 1 12 The electronic conductivity of oxide solid electrolytes is reduced by about 14 times. Figure 5 shown.

[0041] 4) By ion sputtering in Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃. Its activation energy was calculated to be 0.244 eV, which is relatively 12 The activation energy of the oxide solid electrolyte is reduced by 0.081 eV. Figure 6 shown.

[0042] 5) Using metallic sodium as the symmetrical electrode, Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can be stably cycled for 2600 hours, which is comparable to the Na3Zr2Si2PO 12 Compared with oxide solid electrolytes, they show excellent stability to sodium (see Figure 7 ).

[0043] 6) Put Na 3.6 Zr 1.8 (ZnCaScLa) 0.05 Si 2.3 P 0.7 O12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 83.4 mAhg -1 After 500 cycles, the discharge capacity is 70.1 mAh g -1 Compared with Na3Zr2Si2PO in Comparative Example 1 12 Compared with oxide solid electrolytes, it exhibits excellent electrochemical performance (see Figure 8 ). Example 2

[0044] This embodiment Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, ZnO, CaO, Yb2O3, and GeO2 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0045] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0046] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.03×10 -3 S cm -1 .

[0047] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8(ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.2 mA cm -2 high current density.

[0048] 3) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 7.12×10 -9 S cm -1 .

[0049] 4) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.267 eV.

[0050] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1300 hours.

[0051] 6) Put Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 84.7 mAhg -1 After 500 cycles, the discharge capacity is 64.5 mAh g -1 . Example 3

[0052] This embodiment Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CuO, La2O3, HfO2, and Nb2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0053] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0054] Performance testing and battery assembly 1) By ion sputtering in Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.34×10 -3 S cm -1 .

[0055] 2) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.6 mA cm -2 high current density.

[0056] 3) By ion sputtering in Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is tested to be 9.12×10 -9 S cm -1 .

[0057] 4) By ion sputtering in Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.273 eV.

[0058] 5) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1500 hours.

[0059] 6) Put Na 3.4 Zr 1.8 (CuLaHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 76.5 mAhg -1After 500 cycles, the discharge capacity is 57.1 mAh g -1 . Example 4

[0060] This embodiment Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CaO, Y2O3, In2O3, and Sb2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0061] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0062] Performance testing and battery assembly 1) By ion sputtering in Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.81×10 -3 S cm -1 .

[0063] 2) Using metallic sodium as the symmetrical electrode, Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 6.4 mA cm -2 high current density.

[0064] 3) By ion sputtering in Na3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 10.2×10 -9 S cm -1 .

[0065] 4) By ion sputtering in Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.294 eV.

[0066] 5) Using metallic sodium as the symmetrical electrode, Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 900 hours.

[0067] 6) Put Na 3.45 Zr 1.8 (CaYInSb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 78.1 mAhg -1 After 500 cycles, the discharge capacity is 57.8 mAh g -1 . Example 5

[0068] This embodiment Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, ZnO, MgO, Yb2O3, and GeO2 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0069] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0070] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 1.96×10 -3 S cm -1 .

[0071] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 4.4 mA cm -2 high current density.

[0072] 3) By ion sputtering in Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 18.9×10 -9 S cm -1 .

[0073] 4) By ion sputtering in Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.312 eV.

[0074] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 500 hours.

[0075] 6) Put Na 3.55 Zr 1.8 (ZnMgYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 83.2 mAhg -1 After 500 cycles, the discharge capacity is 54.77 mAh g -1 . Example 6

[0076] This embodiment Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, MgO, Sc2O3, HfO2, and Nb2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0077] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0078] Performance testing and battery assembly 1) By ion sputtering in Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.11×10 -3 S cm -1 .

[0079] 2) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 4.2 mA cm -2 high current density.

[0080] 3) By ion sputtering in Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 20.6×10 -9 S cm -1 .

[0081] 4) By ion sputtering in Na 3.4 Zr1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.311 eV.

[0082] 5) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 550 hours.

[0083] 6) Put Na 3.4 Zr 1.8 (MgScHfNb) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 75.8 mAhg -1 After 500 cycles, the discharge capacity is 53.2 mAh g -1 . Example 7

[0084] This embodiment Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, ZnO, Ta2O5, Yb2O3, and GeO2 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0085] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 Oxide solid electrolyte.

[0086] Performance testing and battery assembly 1) By ion sputtering in Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.02×10 -3 S cm -1 .

[0087] 2) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 4.4 mA cm -2 high current density.

[0088] 3) By ion sputtering in Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is tested to be 19.5×10 -9 S cm -1 .

[0089] 4) By ion sputtering in Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.309 eV.

[0090] 5) Using metallic sodium as the symmetrical electrode, Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 600 hours.

[0091] 6) Put Na 3.4 Zr 1.8 (ZnTaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 78.2 mAhg -1 After 500 cycles, the discharge capacity is 54.5 mAh g -1 . Example 8

[0092] This embodiment Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CuO, CaO, Yb2O3, and GeO with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0093] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0094] Performance testing and battery assembly 1) By ion sputtering in Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.34×10 -3 S cm -1 .

[0095] 2) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 8.2 mA cm -2 high current density.

[0096] 3) By ion sputtering in Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 6.91×10 -9 S cm -1 .

[0097] 4) By ion sputtering in Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.293 eV.

[0098] 5) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1700 hours.

[0099] 6) Put Na 3.65 Zr 1.8 (CuCaYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 75.8 mAhg -1 After 500 cycles, the discharge capacity is 56.8 mAh g -1 . Example 9

[0100] This embodiment Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, MgO, ZnO, Yb2O3, and GeO with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0101] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0102] Performance testing and battery assembly 1) By ion sputtering in Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.26×10-3 S cm -1 .

[0103] 2) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 5.6 mA cm -2 high current density.

[0104] 3) By ion sputtering in Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 17.9×10 -9 S cm -1 .

[0105] 4) By ion sputtering in Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.302 eV.

[0106] 5) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 600 hours.

[0107] 6) Put Na 3.65 Zr 1.8 (MgZnYbGe) 0.05 Si 2.4 P 0.6 O12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 75.3 mAhg -1 After 500 cycles, the discharge capacity is 53.9 mAh g -1 . Example 10

[0108] This embodiment Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CaO, MgO, HfO2, and Ta2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0109] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0110] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.17×10 -3 S cm -1 .

[0111] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.8 mA cm -2 high current density.

[0112] 3) By ion sputtering in Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 8.24×10 -9 S cm -1 .

[0113] 4) By ion sputtering in Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.292 eV.

[0114] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1100 hours.

[0115] 6) Put Na 3.55 Zr 1.8 (CaMgHfTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 84.8 mAhg -1After 500 cycles, the discharge capacity is 60.2 mAh g -1 . Embodiment 11

[0116] This embodiment Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CaO, Y2O3, HfO2, and Nb2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0117] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0118] Performance testing and battery assembly 1) By ion sputtering in Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.48×10 -3 S cm -1 .

[0119] 2) Using metallic sodium as the symmetrical electrode, Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 6.2 mA cm -2 high current density.

[0120] 3) By ion sputtering in Na3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 15.4×10 -9 S cm -1 .

[0121] 4) By ion sputtering in Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.296 eV.

[0122] 5) Using metallic sodium as the symmetrical electrode, Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 900 hours.

[0123] 6) Put Na 3.5 Zr 1.8 (CaYHfNb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 77.2 mAhg -1 After 500 cycles, the discharge capacity is 55.5 mAh g -1 . Example 12

[0124] This embodiment Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CuO, Sc2O3, In2O3, and Nb2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0125] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0126] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.81×10 -3 S cm -1 .

[0127] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 6.6 mA cm -2 high current density.

[0128] 3) By ion sputtering in Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 12.4×10 -9 S cm -1 .

[0129] 4) By ion sputtering in Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.287 eV.

[0130] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1000 hours.

[0131] 6) Put Na 3.55 Zr 1.8 (CuScInSb) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 79.6 mAhg -1 After 500 cycles, the discharge capacity is 58.2 mAh g -1 . Example 13

[0132] This embodiment Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CaO, ZnO, GeO2, and Ta2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0133] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0134] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.97×10 -3 S cm -1 .

[0135] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.0 mA cm -2 high current density.

[0136] 3) By ion sputtering in Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 11.4×10 -9 S cm -1 .

[0137] 4) By ion sputtering in Na 3.55 Zr1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.289 eV.

[0138] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 900 hours.

[0139] 6) Put Na 3.55 Zr 1.8 (CaZnGeTa) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 76.8 mAhg -1 After 500 cycles, the discharge capacity is 56.7 mAh g -1 . Embodiment 14

[0140] This embodiment Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CuO, MgO, La2O3, and HfO2 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0141] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 Oxide solid electrolyte.

[0142] Performance testing and battery assembly 1) By ion sputtering in Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.41×10 -3 S cm -1 .

[0143] 2) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.4 mA cm -2 high current density.

[0144] 3) By ion sputtering in Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 3.21×10 -9 S cm -1 .

[0145] 4) By ion sputtering in Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.271 eV.

[0146] 5) Using metallic sodium as the symmetrical electrode, Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 2000 hours.

[0147] 6) Put Na 3.65 Zr 1.8 (CuMgLaHf) 0.05 Si 2.4 P 0.6 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 76.8 mAhg -1 After 500 cycles, the discharge capacity is 62.9 mAh g -1 . Embodiment 15

[0148] This embodiment Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, CaO, ZnO, GeO2, and Ta2O5 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 500 rpm for 10 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0149] (2) The dried powder was ground evenly in an agate mortar and placed in a tube furnace for sintering. The sintering atmosphere was pure oxygen, the sintering temperature was 1000 degrees, and the sintering time was 10 hours. The sintered powder was placed in an agate ball mill again, and zirconium oxide balls were added according to the ball-to-material ratio of 5:1. Anhydrous ethanol was added, and the ball milling speed was 500 rpm. The ball milling time was 10 hours. After the ball milling was completed, the mixed material was placed in a blast drying oven for 80 ℃ drying solvent, get Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 Precursor.

[0150] (3) Weigh a certain mass of Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The precursor was mixed with polyacrylic acid aqueous solution (concentration of 10 mg / ml) (Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The precursor and polyacrylic acid aqueous solution (mass ratio of 50:1) were placed in a customized mold and made into a green body by isostatic pressing. The pressure used was 300MPa and the pressure holding time was 4 minutes. The green body was placed in a tubular furnace for two-stage sintering. The sintering atmosphere was pure oxygen. The first stage sintering temperature was 800 degrees and the sintering time was 1.5 hours. The second stage sintering temperature was 1300 degrees and the sintering time was 7 hours. After annealing, a high-entropy NASICON oxide solid electrolyte sheet was obtained.

[0151] Performance testing and battery assembly 1) By ion sputtering in Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 3.25×10 -3 S cm -1 .

[0152] 2) Using metallic sodium as the symmetrical electrode, Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 7.3mA cm -2 high current density.

[0153] 3) By ion sputtering in Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is tested to be 9.3×10 -9 S cm -1 .

[0154] 4) By ion sputtering in Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.282 eV.

[0155] 5) Using metallic sodium as the symmetrical electrode, Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1300 hours.

[0156] 6) Put Na 3.71 Zr 1.72 (CaZnGeTa) 0.07 Si 2.5 P 0.5 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode were assembled into an all-solid-state battery. The battery was tested for electrochemical performance using a Blue Power CT2001A battery test system. The charge and discharge voltage range was 2.5~3.8 V, the rate was 1C, and constant rate charge and discharge were performed. The initial discharge capacity reached 82.2mAh g -1 After 500 cycles, the discharge capacity is 61.3 mAh g -1 . Example 16

[0157] The difference between Example 16 and Example 2 is that the first stage sintering temperature in step (3) of Example 16 is 400 degrees and the sintering is one hour. The rest is the same as Example 2. 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 .

[0158] Performance testing and battery assembly 1) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 2.44×10 -3 S cm -1 .

[0159] 2) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 6.5 mA cm -2 high current density.

[0160] 3) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 15.47×10 -9 S cm -1 .

[0161] 4) By ion sputtering in Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.303 eV.

[0162] 5) Using metallic sodium as the symmetrical electrode, Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 1000 hours.

[0163] 6) Put Na 3.55 Zr 1.8 (ZnCaYbGe) 0.05 Si 2.3 P 0.7 O 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 2.5~3.8 V, the rate is 1C, and the constant rate charge and discharge is performed. The initial discharge capacity reaches 83.6 mAhg -1 After 500 cycles, the discharge capacity is 60.6 mAh g -1 .

[0164] Comparative Example 1 Comparative Example Na3Zr2Si2PO 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, and NH4H2PO4 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0165] Steps (2) and (3) are the same as in Example 1 to prepare Na3Zr2Si2PO 12 Oxide solid electrolyte.

[0166] Performance testing and battery assembly 1) By ion sputtering on Na3Zr2Si2PO 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 0.36×10 -3 S cm -1 .

[0167] 2) Using metallic sodium as the symmetrical electrode, Na3Zr2Si2PO 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 0.6 mA cm -2 high current density.

[0168] 3) By ion sputtering on Na3Zr2Si2PO 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 35.1×10 -9 S cm -1 .

[0169] 4) By ion sputtering on Na3Zr2Si2PO 12 The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.325 eV.

[0170] 5) Using metallic sodium as the symmetrical electrode, Na3Zr2Si2PO 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can circulate stably for 4 hours.

[0171] 6) Na3Zr2Si2PO 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode were assembled into an all-solid-state battery. The battery was tested for electrochemical performance using a Blue Power CT2001A battery test system. The charge and discharge voltage range was 2.5~3.8 V, the rate was 1C, and constant rate charge and discharge were performed. The initial discharge capacity reached 8.4 mAh g -1 After 500 cycles, the discharge capacity is 5.7 mAh g -1 .

[0172] Comparative Example 2 Na in Comparative Example 2 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The preparation method of the oxide solid electrolyte is as follows: (1) According to the stoichiometric ratio, weigh Na2CO3, ZrO2, SiO2, NH4H2PO4, ZnO, CaO, Yb2O3, and GeO2 with a purity of more than 99% and place them in an agate ball mill. Add zirconium oxide balls according to the ball-to-material ratio of 5:1, add anhydrous ethanol, and mill at a speed of 400 rpm for 8 hours. After the ball milling, place the mixed material in a forced air drying oven at 80°C to dry the solvent.

[0173] Steps (2) and (3) are the same as in Example 1 to prepare Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 Oxide solid electrolyte.

[0174] Performance testing and battery assembly 1) By ion sputtering in Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature ionic conductivity is 1.73×10 -3 S cm -1 .

[0175] 2) Using metallic sodium as the symmetrical electrode, Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The limiting current density was tested under ℃ conditions and can reach 5.2 mA cm -2 high current density.

[0176] 3) By ion sputtering in Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The oxide solid electrolyte sheet is gold-plated on both sides, and its room temperature electronic conductivity is 17.12×10 -9 S cm -1 .

[0177] 4) By ion sputtering in Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12The oxide solid electrolyte sheet was gold-plated on both sides, and its ionic conductivity was tested at -20 ℃ ~ 80 ℃, and its activation energy was calculated to be 0.297 eV.

[0178] 5) Using metallic sodium as the symmetrical electrode, Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The oxide solid electrolyte is used as the electrolyte layer, assembled into a symmetrical battery, and the cycle test is carried out using the Blue Power CT2001A battery test system. The battery has a current density of 5 mA cm -2 It can stably cycle for 900 hours.

[0179] 6) Put Na 3.25 Zr 1.8 (ZnCaYbGe) 0.05 Si2PO 12 The oxide solid electrolyte, Na3V2(PO4)3 positive electrode and metal sodium negative electrode were assembled into an all-solid-state battery. The battery was tested for electrochemical performance using a Blue Power CT2001A battery test system. The charge and discharge voltage range was 2.5~3.8 V, the rate was 1C, and constant rate charge and discharge were performed. The initial discharge capacity reached 76.7 mAh g -1 After 500 cycles, the discharge capacity is 56.8 mAh g -1 .

[0180] By comparing Examples 1-16 with Comparative Example 1, it can be seen that the doping of multiple elements such as Zn, Mg, Cu, Ca, Sc, In, La, Yb, Y, Hf, Ge, Sb, Ta, and Nb is beneficial to improving the ionic conductivity and limiting current density of the solid electrolyte, and has excellent sodium stability, and further using the oxide solid electrolyte to obtain an all-solid-state sodium secondary battery with better long-cycle stability. Examples 5, 6, 7, and 9 do not include Cu, Ca, La, and Yb elements, and the performance of the solid electrolyte prepared therefrom is relatively low relative to other embodiments including one or more of the elements Cu, Ca, La, and Yb. The atomic number of Si in Comparative Example 2 is 2, and its performance relative to Example 2 is reduced. Although Example 16 adopts two-stage sintering, the sintering temperature in the first stage is relatively low, resulting in a decrease in the performance of Example 16 relative to Example 2.

[0181] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0182] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0183] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A high entropy NASICON oxide solid electrolyte, characterized in that: Its chemical formula is Na 3±i Zr 2-x M x Si 2+ y P 1-y O 12 , where 0≤i<1, 0<x<1, 0.25≤y≤0.5, and M is four or more of Zn, Mg, Cu, Ca, Sc, In, La, Yb, Y, Hf, Ge, Sb, Ta, and Nb.

2. A high entropy NASICON oxide solid electrolyte according to claim 1, characterized in that: M is one or more of Cu, Ca, La, and Yb and one or more of Zn, Mg, Sc, In, Y, Hf, Ge, Sb, Ta, and Nb, and the element types of M are four or more.

3. A high entropy NASICON oxide solid electrolyte according to claim 1, characterized in that: The chemical formula is Na 3+i Zr 2-x M x Si 2+y P 1-y O 12 , where 0.4≤i≤0.

9.

4. A high entropy NASICON oxide solid electrolyte according to claim 1, characterized in that: The room temperature ionic conductivity of the NASICON oxide solid electrolyte is ≥1×10 -3 S cm -1 .

5. A high entropy NASICON oxide solid electrolyte according to claim 1, characterized in that: The room temperature ionic conductivity of the NASICON oxide solid electrolyte is 1.9×10 -3 ~8×10 -3 S cm -1 .

6. The method for preparing a high entropy NASICON oxide solid electrolyte according to claim 1, characterized in that: The following steps are involved: (1) According to the general formula Na 3±i Zr 2-x M x Si 2+y P 1-y O 12 , respectively weighing a sodium source, a phosphorus source, a zirconium source, a silicon source and an M ion source in a stoichiometric ratio, performing a first wet mixing and drying, and further performing high temperature sintering, and obtaining a precursor powder after a second wet mixing and drying; (2) Precursor powder is mixed with a binder solution, isostatically pressed to form a green body, and then subjected to two-stage sintering to obtain the high-entropy NASICON oxide solid electrolyte.

7. The preparation method according to claim 6, characterized in that: The wet mixing method is mechanical ball milling or high-energy ball milling, the ball-to-material ratio is (2-6):1, the ball milling speed is 200-600 rpm, the ball milling time is 2-12 hours, and the ball milling solvent is one or more of anhydrous ethanol, isopropanol, n-propanol, acetone, and butanol; The high temperature sintering conditions of step (1) are: 500-1200° C., 2-24 hours in a pure oxygen atmosphere.

8. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of the precursor powder to the binder solution is (10-50): 1, the binder is one or more of polyvinyl alcohol, polyvinyl butyral, polydopamine, and polyacrylic acid; The pressure used for isostatic pressing is 10~700 MPa, and the pressure holding time is 1 min~4 h.

9. The preparation method according to claim 6, characterized in that: In step (2), the two-stage sintering includes a first-stage sintering and a second-stage sintering; The sintering temperature in the first stage is 550~900℃ and the sintering time is 1~4 hours; The second stage sintering temperature is 1100~1300℃, and the sintering time is 2~24 hours; The two-stage sintering is both carried out in a pure oxygen atmosphere.

10. An all-solid-state sodium secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the high entropy NASICON oxide solid electrolyte as claimed in claim 1 or the high entropy NASICON oxide solid electrolyte prepared by the preparation method as claimed in claim 6.

Citation Information

Patent Citations

  • NASICON-structured sodium ion solid electrolyte, preparation method thereof, and solid sodium ion battery

    CN108695552A

  • Fast sodium ion conductor NASICON type solid electrolyte material and preparation method and application thereof

    CN113675462A

  • Mg &lt; 2 + &gt; doped and modified NASCION type sodium ion solid electrolyte and preparation method thereof

    CN114171787A

  • Sodium ion solid electrolyte with NASICON structure as well as preparation method and application of sodium ion solid electrolyte

    CN115832415A

  • High-conductivity sodium ion solid electrolyte composite material as well as preparation method and application thereof

    CN116581368A